Antimycobacterial Activity of Nitrogen Heterocycles Compounds with Indolizine Skeleton - Mangalagiu, Violeta; Danac, Ramona; Olaru, Anda-Mihaela; Diaconu, Dumitrela; Mangalagiu, Ionel I. (Chemistry and Biochemistry: Research Progress Vol. 1, 2025)
During the last decades, tuberculosis (TB), a contagious disease caused by Mycobacterium tuberculosis, become a serious threat threatening against human life and, the phenomena of drug resistance, multidrug-resistant and total drug-resistant to TB complicated the situation even worse. Within this work, a series of thirteen compounds having a monoindolizine mono-salt skeleton was designed and synthesized in order to evaluate their antimycobacterial activity. The synthesis is efficient, involving only three steps: two alkylations and one 3+2 dipolar cycloaddition. The antimicrobial activity against Mycobacterium tuberculosis H37Rv grown under aerobic conditions was evaluated, with eight compounds showing very good antimycobacterial activity. SAR correlation reveals a certain influence of the R substituent from the para position of benzoyl moiety at position 3 of the indolizine skeleton and of the R’ substituent from the para position of benzoyl moiety anchored on the nitrogen atom of the pyridine ring. The most active compounds are those bearing a para-halogen (chlorine or bromine)-benzoyl or a benzoyl moiety at position 3 of indolizine moiety and a para-methyl benzoyl or methoxy (in para or meta position)benzoyl moiety linked to nitrogen atom from pyridine ring. The most active five compounds (namely 6a, 6c, 6d, 6h, 6i) passed the second stage of anti-TB screening, the assay demonstrating that they are potent against both replicating and non-replicating Mtb, have a bactericidal mechanism of action, are active against drug-resistant Mtb strains, present a moderate to good activity against nontuberculous mycobacteria, a good intracellular activity, and a moderate to high cytotoxicity. Remarkably, one compound, namely 6i, have an excellent anti-TB activity in the range of nanomolar, both for MIC and IC50. For the most active compound, the monoindolizine mono-salt 6i, showing a promising anti-TB profile, a complete ADMET study has been performed. Overall the monoindolizine mono-salt 6i seems to be a good hit anti-TB drug candidate, future modifications and optimization on this structure being of high interest for obtaining new anti-tuberculosis drugs.